EXPLORING PERSPECTIVES OF SAUDI HEALTH ASSISTANTS ON ELECTRONIC HEALTH RECORD USE: A QUALITATIVE STUDY - Ahmed Farhan T Alharbi, Saad Fahad M Alshammari, Faisal Helail Aldhafeeri, Salman Shalal Alshammari, Salman Ayed Alhurayji, Sulaiman Mohammad Alshammari, (Chelonian Research Foundation, 2022)
Electronic health records (EHRs) are being widely adopted throughout Saudi Arabian healthcare, yet little is known about the experiences and perspectives of health assistants as frequent EHR users. This exploratory qualitative study aimed to understand the views of Saudi health assistants regarding EHR use through focus group interviews. 12 health assistants from wards at a major hospital discussed EHR benefits, challenges, impacts on clinical workflow, and recommendations for optimization. Results revealed perceived benefits of EHRs including improved legibility and access to patient information compared to paper records, along with key barriers like insufficient initial and ongoing EHR training, disruptions to workflow, increased documentation burden, and suboptimal system design and technical issues. Participants emphasized needs for enhanced skills training on EHR use, greater user-centered system design tailored to the assistant role, and increased involvement of assistants in EHR selection and optimization initiatives at their facilities. Findings provide valuable insights from the Saudi health assistant perspective to inform organizational and system-wide initiatives aimed at improving EHR usability, utility and acceptance among this user group.